ANALISIS SKALA EKONOMIS PADA INDUSTRI KECIL GENTENG ( STUDI KASUS DI DESA KALIBAGOR KECAMATAN SITUBONDO KABUPATEN SITUBONDO ) - ., Suparno; Anggraini, Dian (JEB17 : Jurnal Ekonomi dan Bisnis, 2017)
ABSTRACTThis study entitled "Economic Scale Analysis on Small Industry Roof (Case Study in Kalibagor Village Situbondo Subdistrict Situbondo Regency) aims to determine the economical scale and nature of industrial production from small tile industry in the village of Kalibagor Situbondo District Situbondo regency. It is assumed that the economical scale of small-scale industry of tile maker in Kalibagor Village is in increasing return to scale condition and it is assumed that the nature of small industrial production of tile is labor-intensive. Kalibogor Village as one example of a small industrial center in the manufacture of tile which amounted to 250 business units, with this sample taking the sample with random sampling method of 71 respondents. The data collection research conducted using field study methods with techniques, non-participant observation, structured interviews and documentation. The research was conducted including the type of quantitative descriptive research using multiple regression analysis technique. The results of this study indicate, economical scale of small tile industry in Kalibagor Village Situbondo Situbondo Situbondo is in a state of increasing return to scale, this can be seen from the sum of regression coefficient of labor and capital regression coefficient greater than one. While the nature of industrial production is labor-intensive as shown by the labor regression coefficient is greater than the regression coefficient of capital. The most dominant variable in influencing small scale industrial production of tile maker in Kalibagor Village Situbondo subdistrict of Situbondo Regency is capital variable seen from the largest value of standardized coefficients, so that the capital increase is expected to increase the production of small-scaled tile industry in Kalibagor Village, Situbondo sub-district, Situbondo regency. The Government or the Bank or non-financial institution should be prioritized to lend capital to small scale businessmen of tile craftsmen so that entrepreneurs can develop their business either in the form of credit or others.Â Keywords: economical scale, industrial production properties, increasing return to scale, labor intensiveÂ Â